2
$\begingroup$

$$\lim_{x\to 0} \frac{a^{\tan x} - a^{\sin x}}{\tan x - \sin x}$$

We weren't supposed to do this using L'Hospital's rule

So in the beginning, I added and subtracted 1 from the numerator the get into a standard limit form

$$\frac{a^x-1}{x}.$$

From then on, I got a string of standard limits but it the end, the answer just doesn't seem to match. All the time I get a $0$ and the answer is $\ln(a)$.

$\endgroup$
3
  • $\begingroup$ It's unclear: were you able to get it into the form $\frac{a^x - 1}{x}$ and were unable to solve from there, or were you unable to get it into that form? $\endgroup$
    – Alex Jones
    May 27, 2020 at 1:26
  • 1
    $\begingroup$ @David: If you're improving the title, why not making it actually descriptive? (And as a side note, it's either L'Hospital or L'Hôpital, but it's never L'hopital.) $\endgroup$
    – Asaf Karagila
    May 27, 2020 at 9:53
  • $\begingroup$ Fair enough. But it was definitely an improvement! $\endgroup$ May 27, 2020 at 16:39

4 Answers 4

7
$\begingroup$

We have :\begin{aligned}\lim_{x\to 0}{\frac{a^{\tan{x}}-a^{\sin{x}}}{\tan{x}-\sin{x}}}&=\lim_{x\to 0}{a^{\sin{x}}\frac{a^{\tan{x}-\sin{x}}-1}{\tan{x}-\sin{x}}}\\ &=a^{0}\times \ln{a}\\ &=\ln{a}\end{aligned}

Because $ \lim\limits_{x\to 0}{\frac{a^{\tan{x}-\sin{x}}-1}{\tan{x}-\sin{x}}}=\lim\limits_{y\to 0}{\frac{a^{y}-1}{y}}=\ln{a} $ as you said.

$\endgroup$
2
  • 2
    $\begingroup$ Actually your answer should be the accepted one (+1). $\endgroup$ May 27, 2020 at 3:27
  • 1
    $\begingroup$ This is my preferred approach. +1 Also +1 for @trancelocation. $\endgroup$
    – Paramanand Singh
    May 27, 2020 at 4:50
1
$\begingroup$

You are going on a right track

$\begin{align} \lim_{x\to 0}\frac{a^{\tan x}-a^{\sin x}}{\tan x-\sin x} &=\lim_{x\to 0}\frac{\frac{(a^{\tan x}-1)\tan x}{\tan x}-\frac{(a^{\sin x}-1)\sin x}{\sin x}}{\tan x-\sin x}\\ &=\lim_{x\to 0}\ln a\frac{\tan x-\sin x}{\tan x-\sin x}\\ &=\ln a \end{align}$

$\endgroup$
2
  • $\begingroup$ I don't see how you got the middle line. BTW my edit was to add the "$\lim_{x\to 0}$" to it. $\endgroup$ May 27, 2020 at 2:39
  • 1
    $\begingroup$ The way you move from second expression to third expression is wrong. You can't replace a part of an expression with its limit (here $\log a$) in general. For more details see this answer. The right approach is given in the answer by user CHAMSI. $\endgroup$
    – Paramanand Singh
    May 27, 2020 at 4:49
1
$\begingroup$

$$ \frac{a^{\tan (x)} - a^{\sin (x)}}{\tan( x) - \sin (x)}= \frac{e^{\tan (x)\log(a)} - e^{\sin (x)\log(a)}}{\tan (x) - \sin (x)}\sim \frac{\Big[1+{\tan (x)\log(a)}\Big]- \Big[1+{\sin (x)\log(a)}\Big]}{\tan (x) - \sin (x) }$$ Simplify the numerator.

$\endgroup$
0
$\begingroup$

$$\lim_{x\to 0}\frac{a^{\tan x}-a^{\sin x}}{\tan x-\sin x}$$ $$=\lim_{x\to 0}\frac{e^{\tan x\ln a}-e^{\sin x\ln a}}{\tan x-\sin x}$$ $$=\lim_{x\to 0}\frac{\left(1+\frac{\tan x\ln a}{1!}+\frac{(\tan x\ln a)^2}{2!}+\ldots\right)-\left(1+\frac{\sin x\ln a}{1!}+\frac{(\sin x\ln a)^2}{2!}+\ldots\right)}{\tan x-\sin x}$$ $$=\lim_{x\to 0}\frac{\frac{(\tan x-\sin x)\ln a}{1!}+\frac{(\tan^2 x-\sin^2 x)(\ln a)^2}{2!}+\ldots}{\tan x-\sin x}$$ $$=\lim_{x\to 0}\left(\ln a+\frac{(\tan x+\sin x)(\ln a)^2}{2}+\ldots\right)$$ $$=\ln a$$

$\endgroup$
3
  • $\begingroup$ Lopital in another way $\endgroup$ May 27, 2020 at 17:41
  • $\begingroup$ Yes, but OP asked to solve without L'Hospital rule. $\endgroup$ May 27, 2020 at 17:43
  • $\begingroup$ these series comes by differentiation;By the way your solution is not wrong $\endgroup$ May 27, 2020 at 17:56

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .